1998
DOI: 10.2337/diacare.21.11.1812
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance, type 2 diabetes, and carotid wall thickness: the Insulin Resistance Atherosclerosis Study.

Abstract: We observed considerably greater IMT among persons with established diabetes but no significant increase in persons with IGT. These data suggest that the increased risk of CHD observed in persons with diabetes may largely develop after the onset of overt diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
2
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 0 publications
6
102
2
6
Order By: Relevance
“…Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR. Because glucose intolerance and renal dysfunction are shown to strongly associate with increased IMT, 15,16 it is reasonable that these disease conditions could affect circulating omentin levels. However, the present study suggests that omentin levels are predictive of carotid IMT, independent of glucose levels and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR. Because glucose intolerance and renal dysfunction are shown to strongly associate with increased IMT, 15,16 it is reasonable that these disease conditions could affect circulating omentin levels. However, the present study suggests that omentin levels are predictive of carotid IMT, independent of glucose levels and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…20 This fi nding contrasts with the Insulin Resistance Atherosclerosis Study, which included whites, African Americans, and Latinos and reported no difference in IMT values between those with normal and impaired glucose tolerance. 25 An explanation for this ethnic difference could be the degree of insulin resistance in the South Asians versus the other ethnic groups that may lead to greater endothelial dysfunction 26 and earlier subclinical atherosclerosis. 27,28 This fi nding supports the "ticking clock" hypothesis 29 that cardiovascular disease may begin before the onset of clinical diabetes in Indians.…”
Section: Resultsmentioning
confidence: 99%
“…This might explain why IMT in our study and in other studies was a weaker correlate of diabetes. For instance in a recent paper from the investigators of the Insulin Resistance Atherosclerosis Study, only subjects with established Type II diabetes but not those with IGT or newly diagnosed Type II diabetes showed a marginally increased IMT after adjustment for confounding factors [63].…”
Section: Discussionmentioning
confidence: 99%